Pembelajaran Problem-Based Learning Berbantuan Media Educaplay untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Umi Fitrotun; Ahmad Khoiri; Vava Imam Agus Faisal (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Critical thinking skills are essential in 21st-century physics education. However, learning processes that are still teacher-centered have hindered the optimal development of students’ critical thinking skills. The Problem Based Learning (PBL) model assisted by Educaplay media can serve as an alternative learning approach that enhances student engagement through interactive activities and problem-solving. This study aimed to determine the effect of the PBL model assisted by Educaplay on students’ critical thinking skills in the topic of thermal expansion. The study employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest  control group design. The research sample consisted of two eleventh-grade classes at MAN 2 Wonosobo selected through purposive sampling techniques. Data analysis was conducted using normality tests, homogeneity tests, independent sample t-tests, and N-Gain analysis. The results showed that the implementation of the PBL model assisted by Educaplay had a positive effect on students’ critical thinking skills. The average N-Gain score of the experimental class was higher than that of the control class. This study contributes to the development of technology-based physics learning to improve students’ higher-order thinking skills.